Plans as Situated Action: An Activity Theory Approach to Workflow Systems - Bardram, Jakob (DAIMI Report Series, 1997)
Within the community of CSCW, the notion and nature of workflow systems as prescriptions of human work has been debated and criticised. Based on the work of Suchman (1987) the notion of situated action has often been viewed as opposed to planning work. Plans, however, do play an essential role in realising work. Based on experiences from designing a computer system that supports the collaboration within a hospital, this paper discusses how plans themselves are made out of situated action, and in return are realised in situ. Thus, work can be characterised as situated planning. This understanding is backed up by Activity Theory, which emphasises the connection between plans and the contextual conditions for realising these plans in actual work.